Born This Day: A Book of Birthdays and Quotations of Prominent People Through the Centuries - Nowlan, Robert A. (McFarland & Co., 2007)
"For each date, a diverse dozen speakers were chosen based on prominence; the quality of the quotation; the uniqueness of the speaker with relation to gender, time period, nationality and vocation; and conflicting social, political, religious or philosophical background. Includes a quotation from each person that allows a glimpse of their personality"–Provided by publisher.
Keywords: Quotations; English; Birthday books; Literary calendars; dept.mat; faculty_collection